Liberalism and Transformation The Global Politics of Violence and Intervention - Tatum, Dillon (University of Michigan Press, 2021)
Liberalism and Transformation is the first scholarly work that explores the historical, philosophical, and intellectual development of global liberalism since the nineteenth century in the context of the deployment of violence, force, and intervention. Using an approach that includes interpretive and contextual analysis of texts from writers, philosophers, and policy-makers across nearly two centuries, as well as historiographical and historical analysis of archival documents (some of which have been recently declassified) and other media, Liberalism and Transformation narrates the messy history of emancipatory liberalism and its engagement with issues of war and peace. The book contributes to both a rethinking of liberal democracy and its relationship to world politics, as well as the effects of liberal internationalism on global processes. Furthermore, Liberalism and Transformation invites readers to reflect on global ethics and transformation in world politics. In the first place, it shows how ethical imaginings of the world have direct effects on actions of transformative importance. In the second place, it suggests that discourses are fluid, changing, and complex.